2008
DOI: 10.1017/s0268416008006759
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Clandestine Marriages Act: three case-studies in conformity

Abstract: This article examines the extent of compliance with the Clandestine Marriages Act 1753 through three parish studies. It demonstrates that the vast majority of the sample cohort of parents whose children were baptized in church, and indeed of couples living together, had married in church as required by the 1753 Act, and shows how the proportion of marriages traced rises as more information about the parties becomes available. Through a study of settlement examinations, the article posits an explanation of why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The initial investigation of couples' marital status was carried out using the internet-based International Genealogical Index (IGI). Previous studies had suggested that a number of marriages would not be picked up by such means because of misspellings or because the records of the parish in question had not been transcribed on to the IGI; experience had also shown that the data on the IGI needed to be verified against the original parish registers (Probert and D'Arcy-Brown 2008). A week was therefore spent examining a combination of transcripts and microfiches at Kendal Record Office in April 2010 (during which the occasionally inclement weather provided graphic illustration of what 18th-century residents would have experienced even when travelling short distances).…”
Section: The Sample and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The initial investigation of couples' marital status was carried out using the internet-based International Genealogical Index (IGI). Previous studies had suggested that a number of marriages would not be picked up by such means because of misspellings or because the records of the parish in question had not been transcribed on to the IGI; experience had also shown that the data on the IGI needed to be verified against the original parish registers (Probert and D'Arcy-Brown 2008). A week was therefore spent examining a combination of transcripts and microfiches at Kendal Record Office in April 2010 (during which the occasionally inclement weather provided graphic illustration of what 18th-century residents would have experienced even when travelling short distances).…”
Section: The Sample and Methodologymentioning
confidence: 99%
“…The difference between the two figures is accounted for by a small but significant minority of couples for whom a marriage has been traced in a more distant parish. Other studies confirm that at least a significant minority of the population were highly mobile, and that a couple who married in Berwick-upon-Tweed might well turn up in Bradford-upon-Avon (Probert and D'Arcy-Brown 2008). Were, for example, the Robert and Mary Machell who were living in the parish of Brampton in 1787 the same couple that tied the knot in Whitehaven in 1769?…”
Section: The Findings Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in eighteenth‐ and nineteenth‐century population history are abundant. Probert and Brown offer two articles on the Clandestine Marriages Act, 1753. Widespread compliance resulted not primarily from obedience to the Act but from relatively high levels of Church marriage preceding the statute.…”
Section: (Iv) 1700–1850
Peter Kirby
University Of Manchestermentioning
confidence: 99%
“…1 Rebecca Probert's recent work on the impact of the Marriage Act has tended to downplay somewhat the impact of clandestine marriage before this date. 2 While it is true that such marriages were not evenly available throughout seventeenth-and eighteenth-century England, they were a major factor in the huge metropolitan marriage market. Jeremy Boulton drew attention to the effect on parochial registration of the unique nature of marriage availability in London in two important papers published in the early 1990s.…”
Section: Introductionmentioning
confidence: 99%